2008
DOI: 10.1183/09031936.00117507
|View full text |Cite
|
Sign up to set email alerts
|

Severity of obstructive sleep apnoea/hypopnoea syndrome and subsequent waking EEG spectral power

Abstract: It is well known that most patients with obstructive sleep apnoea/hypopnoea syndrome (OSAHS) suffer sleepiness, although the underlying mechanisms of this relationship remain unclear. The present study examined the relationship between nocturnal variables and the subsequent waking electroencephalogram (EEG), in order to determine if sleepiness was related to OSAHS severity and due to sleep fragmentation or to nocturnal hypoxaemia.In total, 12 moderate-to-severe OSAHS patients underwent a total sleep night foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In a 40-hour sleep deprivation study, theta power was increased as wake time was prolonged and the increase of theta power paralleled the increase of subjective sleepiness [27]. Also, correlations between EEG spectral power and sleepiness were reported in healthy subjects during 24-hour sustained wakefulness [24]. In the current study, a relatively high correlation was observed between changes of EEG slowing and daytime sleepiness measured by ESS.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In a 40-hour sleep deprivation study, theta power was increased as wake time was prolonged and the increase of theta power paralleled the increase of subjective sleepiness [27]. Also, correlations between EEG spectral power and sleepiness were reported in healthy subjects during 24-hour sustained wakefulness [24]. In the current study, a relatively high correlation was observed between changes of EEG slowing and daytime sleepiness measured by ESS.…”
mentioning
confidence: 60%
“…Nocturnal hypoxia, rather than daytime sleepiness has been suggested as an underlying mechanism of EEG slowing in OSAS [24]. In conditions other than OSAS, such as hypobaric and hypoxic conditions generated by a low pressure chamber, hypobaric hypoxia induced an increase in relative delta and theta activity and a decrease in relative alpha activity [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Not only the slowing ratio, some researchers even found that AHI and α power were positively correlated in OSA patients, and oxygen desaturation index (ODI) was positively correlated with θ and α power. In addition, they found that daytime alertness efforts were related to ArI, and daytime sleepiness was related to ODI (49). Other studies found no significant correlation between OSA severity and any rsEEG rhythm (26,27,49,50).…”
Section: Application Of Rseeg In Osamentioning
confidence: 95%
“…In addition, they found that daytime alertness efforts were related to ArI, and daytime sleepiness was related to ODI (49). Other studies found no significant correlation between OSA severity and any rsEEG rhythm (26,27,49,50). Only two studies found a significant correlation between subjective sleepiness and rsEEG power.…”
Section: Application Of Rseeg In Osamentioning
confidence: 98%
See 1 more Smart Citation